Effects of Peanuts and Pistachios on Gut Microbiota and Metabolic Syndrome: A Review - Campos, Stéphani Borges; Oliveira Filho, Josemar Gonçalves de [UNESP]; Salgaço, Mateus Kawata [UNESP]; Jesus, Marisa Helena De; Egea, Mariana Buranelo (MDPI, 2023)
There is growing evidence that the gut microbiota is associated with various aspects of human health, including immune system regulation, vitamin synthesis, short-chain fatty acid production, etc. Peanuts and pistachios are foods rich in protein, unsaturated fatty acids, vitamins, polyphenols, and other dietary components that have been shown to benefit the gut microbiota. Therefore, this review aims to describe the effects of consuming peanuts and pistachios on the gut microbiota and the potential role of these microbiota in human health. This review suggests that the consumption of peanuts or pistachios can demonstrate the potential to exert a beneficial effect on the gut microbiota by promoting the growth of beneficial gut bacteria that produce, for example, short-chain fatty acids that are beneficial for human health. In the case of peanuts, in particular, the possible modulation of the microbiota is associated with an improvement in the risk factors of metabolic syndrome and the inflammatory process triggered by a high-fat diet.
Keywords: dietary impact; functional food; gut health; prebiotics